Comparison of perioperative outcomes between robotic-assisted and video-assisted thoracoscopic surgery for mediastinal masses in patients with different body mass index ranges: A population-based study - Li, Rongyang; Ma, Zheng; Qu, Chenghao; Qiu, Jianhao; Wang, Kun; Yue, Weiming; Tian, Hui (Frontiers in Surgery, 2022)
Background The effectiveness of robotic-assisted thoracoscopic surgery (RATS) for mediastinal masses has not been fully evaluated. This study aimed to compare the perioperative outcomes between RATS and video-assisted thoracoscopic surgery (VATS) for mediastinal masses, and then explore which group of people would benefit more from RATS. Methods This retrospective study compared the perioperative outcomes of patients with mediastinal masses who underwent RATS and VATS from September 2018 to December 2021. Subgroup analysis were performed according to body mass index (BMI) ranges. Results A total of 212 patients with mediastinal masses (106 RATS cases and 106 VATS cases) were included. Compared with the VATS group, the RATS group had a significantly reduced incidence of overall postoperative complications (5.7% vs. 14.2%, p = 0.039), complications of grade II or less (3.8% vs. 12.3%, p = 0.023), and pneumonia (2.8% vs. 9.4%, p = 0.045). Hospitalization costs were significantly higher in the RATS group (¥ 49350.0 vs. ¥ 32551.9, p < 0.001). There was no significant difference in operation duration, intraoperative estimated blood loss, postoperative chest tube drainage volume, NRS pain score, day of chest tube removal, complications of grade III or more, or in-hospital mortality rate (p > 0.05). Subgroup analysis indicated that the incidence of overall postoperative complications (3.1% vs. 15.2%, p = 0.017), complications of grade II or less (1.5% vs. 12.1%, p = 0.033) and postoperative length of stay (4 days vs. 4.5 days, p = 0.046) were significantly reduced in the RATS group for overweight and obese patients (BMI ≥ 24 kg/m2), while these differences became insignificant in the BMI < 24 kg/m2 subgroup. Conclusion RATS could reduce the incidence of postoperative complications, shorten the postoperative length of stay and might be a more cost-effective surgical treatment for overweight and obese patients with mediastinal masses.